2013
DOI: 10.1002/cpp.1866
|View full text |Cite
|
Sign up to set email alerts
|

Initial Psychometric Evaluation of the Moral Injury Questionnaire—Military Version

Abstract: Military service can confront service members with experiences that undermine their core sense of humanity and violate global values and beliefs. These types of experiences increase the risk for posttraumatic maladjustment in this population, even when accounting for rates of exposure to life threat traumas. Moral injury is an emerging construct to more fully capture the many possible psychological, ethical, and spiritual/existential challenges among persons who served in modern wars and other trauma-exposed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
246
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(271 citation statements)
references
References 37 publications
19
246
1
4
Order By: Relevance
“…The empirical three‐path model of the psychological mechanisms from PMIEs to PTSS that was found in our study validates the conceptualized MI model suggested by Litz and colleagues () and agrees with several studies in the field (e.g. Currier et al., ; Currier et al., ).The integration of the model and our data suggest this chain of reactions, MI experiences induce depressive attributes among veterans who are aware of the discrepancy between their morals and the actual moral violation. These attributes are reflected in perception of global, internal and stable personality deficits that facilitate experiences of trauma‐related guilt, shame and self‐disgust.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The empirical three‐path model of the psychological mechanisms from PMIEs to PTSS that was found in our study validates the conceptualized MI model suggested by Litz and colleagues () and agrees with several studies in the field (e.g. Currier et al., ; Currier et al., ).The integration of the model and our data suggest this chain of reactions, MI experiences induce depressive attributes among veterans who are aware of the discrepancy between their morals and the actual moral violation. These attributes are reflected in perception of global, internal and stable personality deficits that facilitate experiences of trauma‐related guilt, shame and self‐disgust.…”
Section: Discussionsupporting
confidence: 92%
“…Currier et al. () recently provided preliminary evidence for the validity (factorial, convergent, and incremental) and utility of the instrument for additional research and clinical work with military populations. Internal consistency was good for the subscale of causes ( α = 0.83) and moderate for effects ( α = 0.64).…”
Section: Methodsmentioning
confidence: 99%
“…Not until very recently have any instruments been developed to measure it. For instance, the Moral Injury Event Scale (MIES; Nash et al, 2013) and the Moral Injury Questionnaire – Military Version (MIQ-M; Currier et al, 2015) were not published until 2013 and 2015, respectively, well after the present dataset was collected. Until that time, researchers identified moral injury based on the nature of the trauma (namely that the traumatized violated moral or ethical standards) and associated guilt (for example, see Stein et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, “I saw things that were morally wrong” and “I acted in ways that violated my own morals or values.” Some items also included reactions to these experiences (e.g., I am troubled by having acted in ways that violated my own morals or values) as well as three items that focus on the service member's feeling of betrayal (e.g., I feel betrayed by leaders who I once trusted). Currier, Holland, Drescher, and Foy () generated an alternative measure of exposure to potentially morally injurious events called the Moral Injury Questionnaire, Military Version (MIQ‐M), using items designed to tap into the types and responses to morally injurious events highlighted in Drescher et al. ().…”
Section: Introductionmentioning
confidence: 99%